(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
ABSTRACT: This article analyzes the jurisdiction of the Labor Courts in disputes involving public employees, in light of the legal thesis established by the Brazilian Federal Supreme Court (STF) in Theme 1.143 of General Repercussion. The research begins with a historical and normative overview of the public employment regime, contrasting the adoption of CLT-based employment contracts within the scope of direct, autarchic, and foundational public administration with the principles of public law. Subsequently, the article examines the expansion of the material jurisdiction of the Labor Justice introduced by Constitutional Amendment No. 45/2004, especially concerning the inclusion of the expression "labor relation" in Article 114 of the Federal Constitution. In a third stage, an in-depth analysis is conducted on the decision rendered in Extraordinary Appeal No. 1.288.440/SP, identifying its reasoning, inconsistencies with previous STF jurisprudence, and the risks posed by the expression "benefit of an administrative nature" to legal certainty. The methodology applied consists of bibliographic research and case law analysis, based on specialized legal doctrine and judicial precedents. It concludes that the thesis established by the Court disregards a significant portion of the critical issues raised and may jeopardize the effectiveness of judicial protection afforded to public employees. Keywords: Public Employee; Labor Justice; Constitutional Jurisdiction; STF Theme 1.143; Constitutional Amendment No. 45/2004.